Evaluation of Rheum Turkestanicum in Hexachlorobutadien-Induced Renal Toxicity - Boroushaki, Mohammad Taher; Fanoudi, Sahar; Rajabian, Arezoo; Boroumand, Samaneh; Aghaee, Azita; Hosseini, Azar (Drug Research, 2019)
Hexachlorobutadien is nephrotoxic agent in rodents. The mechanism of toxicity includes generation of free radicals, depletion of thiol groups and production of toxic metabolites. Antioxidant compounds may reduce HCBD-nephrotoxicity. In this research we investigated the effect of Rheum turkeatanicum extract against HCBD-toxicity. The animals were divided to 4 groups which were including control (saline, 1 mL/kg), HCBD (100 mg/kg) and treatment groups which received extract at doses 100 and 200 mg/kg. The extract were administered as intraperitoneally (i.p.) 1 h before HCBD injection (i.p.). The animals were anesthetized by ether, 24 h after HCBD administration. The results showed elevation of serum creatinine, serum urea, urinary protein, urinary glucose, malondialdehyde levels in kidney and reduction of thiol in kidney by HCBD. The histopathological studies showed that there was apoptosis and necrosis in HCBD treated groups. Administration of R.turkestanicum reduced HCBD toxicity. The extract reduced hitopathological changes in kidney. It may be concluded that the nephroprotective effect of extract may be due to different mechanisms such as antioxidant activity or by decreasing the toxic metabolites of HCBD or inhibition of enzymes which are involved in the bioactivation of HCBD such as glutathione-S-transferase (GST) or cysteine-S-conjugate β-lyase.
Keywords: rheum turkestanicum; hexachlorobutadien; renal toxicity; oxidative stress; malondialdehide